2018
DOI: 10.1098/rsos.180811
|View full text |Cite
|
Sign up to set email alerts
|

Porous poly- l -lactide-co-ɛ-caprolactone scaffold: a novel biomaterial for vaginal tissue engineering

Abstract: The surgical reconstruction of functional neovagina is challenging and susceptible to complications. Therefore, developing tissue engineering-based treatment methods for vaginal defects is important. Our aim was to develop and test a novel supercritical carbon dioxide foamed poly-l-lactide-co-ɛ-caprolactone (scPLCL) scaffold for vaginal reconstruction. The scaffolds were manufactured and characterized for porosity (65 ± 4%), pore size (350 ± 150 µm) and elastic modulus (2.8 ± 0.4 MPa). Vaginal epithelial (EC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 55 publications
(76 reference statements)
4
30
2
Order By: Relevance
“…15 Examples of biodegradable polymers that are resorbed overtime frequently used in regenerative medicine [16][17][18] include polyglycolic acid (PGA), polylactide (PLA), polylactic-co-glycolic acid (PLGA), poly-ε-caprolactone (PCL), poly(D,L-lactide) (PDLLA) and additional copolymers and composites. 19,20 Although scaffold degradation is beneficial, undesired effects caused by degradation products via the formation of small chain carboxylic acids may change the local pH and cause inflammation 21,22 or in some cases as occurs within PLA, acidic degradation products may be toxic. 17 Methods developed for the production of these porous polymeric materials include electrospinning, phase separation and porogen leaching.…”
Section: Introductionmentioning
confidence: 99%
“…15 Examples of biodegradable polymers that are resorbed overtime frequently used in regenerative medicine [16][17][18] include polyglycolic acid (PGA), polylactide (PLA), polylactic-co-glycolic acid (PLGA), poly-ε-caprolactone (PCL), poly(D,L-lactide) (PDLLA) and additional copolymers and composites. 19,20 Although scaffold degradation is beneficial, undesired effects caused by degradation products via the formation of small chain carboxylic acids may change the local pH and cause inflammation 21,22 or in some cases as occurs within PLA, acidic degradation products may be toxic. 17 Methods developed for the production of these porous polymeric materials include electrospinning, phase separation and porogen leaching.…”
Section: Introductionmentioning
confidence: 99%
“…Four different PLA scaffolds with various degrees of fiber alignment were constructed to mimic the three-dimensional architecture of human fascia, and the results showed that the bulk density, Young’s modulus, and UTS were significantly increased from PLA-random to PLA-aligned scaffolds, and ADSCs grew well on scaffolds with aligned fibers, produced the largest amount of total collagen, and maintained the strength and stiffness without changes after 2 weeks of culture in vitro ( Roman et al, 2016 ). The scPLCL is a potential scaffold material for vaginal tissue engineering, vaginal epithelial (VE), and stromal cells (SCs) that attached and maintained viability on scPLCL ( Sartoneva et al, 2018 ). The comparison of PLGA/PCL films with different fiber diameters suggested that the fiber diameter affects cell behavior, mechanical properties, and cellular infiltration ECM deposition ( Vashaghian et al, 2016 ).…”
Section: Scaffoldsmentioning
confidence: 99%
“…Macroporous PLCL scaffolds prepared by melt-extrusion have been shown to be biocompatible with vaginal stromal cells (SCs) and epithelial cells (ECs), and have therefore been applied for vaginal tissue engineering [ 161 ]. These scaffolds had pore sizes matching the stiffness of pre-menopausal women’s vaginas.…”
Section: Application Of New Alternative Meshes For Pop Treatmentmentioning
confidence: 99%